Morphology and Mechanical Properties of Plantar Fascia in Flexible Flatfoot: A Noninvasive In Vivo Study - Qian, Zhihui; Jiang, Zhende; Wu, Jianan; Chang, Fei; Liu, Jing; Ren, Lei; Ren, Luquan (Frontiers in Bioengineering and Biotechnology, 2021)
Plantar fascia plays an important role in human foot biomechanics; however, the morphology and mechanical properties of plantar fascia in patients with flexible flatfoot are unknown. In this study, 15 flexible flatfeet were studied, each plantar fascia was divided into 12 positions, and the morphologies and mechanical properties in the 12 positions were measured in vivo with B-mode ultrasound and shear wave elastography. Peak pressures under the first to fifth metatarsal heads were measured with FreeStep. Statistical analysis included 95% confidence interval, intra-group correlation coefficient, one-way analysis of variance, and least significant difference. The results showed that thickness and Young's modulus of plantar fascia were the largest at the proximal fascia and decreased gradually from the proximal end to the distal end. Among the five distal branches of the fascia, the thickness and Young's modulus of the second and third distal branches were larger. The peak pressures were also higher under the second and third metatarsal heads. This study found a gradient distribution in that the thickness and Young's modulus gradient decreased from the proximal end to the distal end of plantar fascia in the longitudinal arch of flexible flatfeet. In the transverse arch, the thickness and Young's modulus under the second and third distal branches were larger than those under the other three distal branches in flexible flatfoot, and the peak pressures under the second and third metatarsal heads were also larger than those under the other three metatarsal heads in patients with flexible flatfoot. These findings deepen our understanding of the changes in biomechanical properties and may be meaningful for the study of pathological mechanisms and therapy for flexible flatfoot.